0.03(2c-50)=-0.6(c-3)

Simple and best practice solution for 0.03(2c-50)=-0.6(c-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.03(2c-50)=-0.6(c-3) equation:


0.03(2c-50)=-0.6(c-3)

We simplify the equation to the form, which is simple to understand
0.03(2c-50)=-0.6(c-3)

Reorder the terms in parentheses
+( + 0.06c-1.5)=-0.6*(c-3)

Remove unnecessary parentheses
+ 0.06c-1.5=-0.6+*(+c-3+)

Reorder the terms in parentheses
+ 0.06c-1.5=+(-0.6c+1.8)

Remove unnecessary parentheses
+ 0.06c-1.5=-0.6c+1.8

We move all terms containing c to the left and all other terms to the right.
+ 0.06c + 0.6c=+1.8+1.5

We simplify left and right side of the equation.
+ 0.66c=+3.3

We divide both sides of the equation by 0.66 to get c.
c=5

See similar equations:

| f(0.5)=-4(x)+3 | | 30p-6=144 | | (x-84)=0.5 | | 3t+4=5t-10 | | 67/8-(-121/3)= | | 4x^2+10x+25=41 | | X^2+100x=9600 | | 23a-25a=2a | | 9x+1=x+6 | | 2(x-5)+4=10 | | 3x^2+5x-13=12 | | 14/25x15/52x8/21 | | -14h=13h-17 | | 3(h)=6 | | 1/2(16-2h)=11 | | 18-(-21)= | | 3x+4x-16+11=23 | | 2-4q=2+5q | | x/-4=-12 | | 2y-4=1 | | x+4+6=26-3x | | 1/4+1/4h=4 | | 2+9t=8t+7 | | 23=2y-13 | | 4x-2(x+5)=6 | | 24-3n-7=20 | | 6/5*(-10*8) | | x^2-8x+12=(x-2) | | 8x-3x+3=x-6+9 | | 210+500=s | | 9x+x-7=13 | | -12-10j=-9j |

Equations solver categories